Next‐generation TCR sequencing – a tool to understand T‐cell infiltration in human cancers1. Issue 4 (21st October 2016) - Poschke, Isabel; Flossdorf, Michael; Offringa, Rienk
Abstract: Tumour‐infiltrating lymphocytes (TILs) are known to mediate potent anti‐tumour activity. As T‐cell‐based therapies start to reach clinical practice, it becomes increasingly important to understand what characterizes a successful anti‐tumour T‐cell response and to exploit this knowledge for patient stratification. Next‐generation sequencing of T‐cell receptors (TCRs) promises to provide insights into the complexity of the tumour T‐cell infiltrate that go beyond the phenotypic level. A recent study by Chen et al made use of this novel technology to demonstrate that the TIL repertoire of oesophageal squamous cell carcinoma patients is distinct from that of non‐tumour sites and is characterized by significant intratumoural heterogeneity. This study illustrates the great potential of the method and addresses several technical and biological hurdles that need to be considered. Careful sampling, normalization, and error correction will be required to optimally use TCR sequencing to answer biological questions and define predictive biomarkers, e.g. for cancer immunotherapy. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd. Abstract : Linked Article:Chen Z et al. J Pathol 2016; 239: 450–458 .